Conceptual Design of Reality Learning Media (RLM) Model Based on Entertaining and Fun Constructs - Ariffin, Abdul Mutalib (2009)
Many eLearning materials (eLM) have been developed for use in education and training. However, studies report that the investments on the courseware projects do not show good returns. Furthermore, the use and perception of teachers and students on eLM, such as courseware on CDs, are very low. In fact, many schools have stopped using courseware in the classrooms. Many factors were identified influencing the disadvantages of courseware implementation in eLearning; nevertheless the way learning content in the eLM is blended and presented to learners is seen as one of the reasons. Existing eLM are found to be not entertaining and not invoking fun, making learners feel bored. In Interaction Design, although many guidelines have stated entertaining and fun as two important design elements, many developers still produced contents that failed to include these elements. One possible reason for this is the nature of fun and entertaining that are difficult to be realized without technical skills and creativity. This leads to the following research questions: (1) How to ensure that learning content is perceived entertaining and invoking fun by the end users?, (2) Can entertaining and fun learning material be effective?, and (3) How to enable instructors especially the non-technically-skilled to produce eLM that are considered entertaining and invoking fun? Answering these questions leads this study to propose a conceptual design model of eLM which is able to ensure content is entertaining and invoking fun as perceived by the end users. Inspired by the famous reality TV shows, the proposed model is called Reality Learning Media (RLM). Therefore, the aim of the study is to propose a conceptual design model of RLM. To accomplish that, four specific objectives are formulated: (1) To determine the components of RLM, (2) To propose the conceptual design model of RLM, (3) To validate the conceptual design model of RLM through prototyping, and (4) To investigate user experience of RLM in terms of entertaining, fun, and effectiveness. Comparative analysis, peer and expert reviews, content analysis, prototyping, and experimental studies are used to accomplish the objectives and aim. General findings show that RLM is perceived entertaining; in fact it is more entertaining than video and courseware. In addition, hypotheses-specific testings using one sample t-Test, independent samples t-Test, and ANOVA reveal that regardless of gender, academic achievement levels, and other eLM experience (before learning with RLM), respondents perceived RLM as entertaining and fun. Not only that, RLM is proven to be effective in delivering learning contents. The main contributions of this study are the concept of reality video that has been put forward, the development of the conceptual design model together with the prototypes of the RLM. Apart from these, the recording techniques for RLM and the validated instrument measuring entertaining and fun are also significant contributions to the body of knowledge.